New natural dyes from red prickly pear produced by addition of metal ions and their application in textile. - Ali, N. F. (International Journal of Agricultural Technology, 2025)
Sicily produces 94% of Italy’s farmed crops. The tropical or subtropical plant Opuntia ficus-indica (L.) Mill. is cultivated in regions such as the Mediterranean and Central America is used to make the natural dye from the fruits of red prickly cactus pear trees. Where it constructs a good source for food. Betaline pigment extracted and used for synthesis of three new metal complex dyes by addition of bivalent metal ions as copper, cobalt and nickel. These dyes are used for dyeing wool fibers using microwave heating and conventional technique Investigations were conducted into the characteristics of the dyed wool fibers, including dye concentration, pH, color strength, color data, and fastness. The results demonstrated that wool fibres have good colour strength and fastness characteristics. The antibacterial action against a few harmful bacteria and fungus was indicated that the antimicrobial activity of the natural dyes was good results. The metal complex dyes from betaline extracted from red prickly were actively against Staphylococcus aureus, Pseudomonas aeruginosa, Aspergillus niger and Escherichia coli.